2015
DOI: 10.3347/kjp.2015.53.5.535
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Schistosomiasis and Soil-Transmitted Helminthiasis Control over Five Years on Kome Island, Tanzania

Abstract: Integrated control strategies are important for sustainable control of schistosomiasis and soil-transmitted helminthiasis, despite their challenges for their effective implementation. With the support of Good Neighbors International in collaboration with National Institute of Medical Research, Mwanza, Tanzania, integrated control applying mass drug administration (MDA), health education using PHAST, and improved safe water supply has been implemented on Kome Island over 5 years for controlling schistosomiasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 16 publications
1
28
1
3
Order By: Relevance
“…Most studies reported more than one outcome as shown in S4 and S5 Tables. Of the 25 studies involving intersectoral collaboration which measured pre-post-outcomes compared against disease indicators, such as the number of cases or incidence or prevalence of malaria (15 studies) [ 4 , 30 43 ], dengue (four studies) [ 44 47 ], schistosomiasis (two studies) [ 48 , 49 ], zika (one study) [ 50 ], Japanese encephalitis (one study) [ 51 ], and leishmaniasis (one study) [ 52 ]. Amongst the 16 studies which measured vector variables (adult density, pupae or larval indices) as outcomes eleven studies were dengue [ 44 , 46 , 47 , 53 60 ], followed by two studies on schistosomiasis [ 48 , 49 ], and one on malaria [ 4 ] and on Chagas diseases [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies reported more than one outcome as shown in S4 and S5 Tables. Of the 25 studies involving intersectoral collaboration which measured pre-post-outcomes compared against disease indicators, such as the number of cases or incidence or prevalence of malaria (15 studies) [ 4 , 30 43 ], dengue (four studies) [ 44 47 ], schistosomiasis (two studies) [ 48 , 49 ], zika (one study) [ 50 ], Japanese encephalitis (one study) [ 51 ], and leishmaniasis (one study) [ 52 ]. Amongst the 16 studies which measured vector variables (adult density, pupae or larval indices) as outcomes eleven studies were dengue [ 44 , 46 , 47 , 53 60 ], followed by two studies on schistosomiasis [ 48 , 49 ], and one on malaria [ 4 ] and on Chagas diseases [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 50 articles, intersectoral collaboration with an intervention to mobilize community and health education was the most common. The interventions implemented through the collaboration between the sectors varied from providing human or financial resources, designing to executing an intervention, developing policy and mobilizing communities (24 studies) [ 30 , 32 , 35 , 43 – 45 , 47 50 , 53 58 , 60 65 , 68 , 72 ], followed by diagnosis and treatment (12 studies) [ 35 , 36 , 39 43 , 49 , 52 , 68 – 71 ], prevention method (IRS and LLINs distribution (11 studies) [ 31 , 35 37 , 39 , 41 , 43 , 66 68 , 73 ], surveillance, monitoring and evaluation (nine studies) [ 35 , 38 42 , 52 , 68 , 69 ], mass drug administration (four studies) [ 48 , 72 , 75 , 76 ], cross border collaboration (four studies) [ 35 , 40 , 43 , 52 ], two studies for research [ 40 , 51 ] and one study for advocacy and legislation […”
Section: Resultsmentioning
confidence: 99%
“…The presence of STH and SCH co-infections shows the efficiencies that might be gained with an integrated control strategy. Indeed, in the past, integrated control has led to impressive reductions in prevalence and related morbidity [27]. In addition to integrating control against various parasites, the delivery of different types of parasite control might also be integrated.…”
Section: Discussionmentioning
confidence: 99%
“…In Buchosa District, the study was conducted at Kome Island. The selection of the study areas was based on the accessibility and the past history of preventive chemotherapy (PC) against STH and schistosomiasis through school-based and community-based approaches [13,14].…”
Section: Methodsmentioning
confidence: 99%